2015
DOI: 10.1111/cas.12841
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled liposome imaging determines an indication for liposomal anticancer agent in ovarian cancer mouse xenograft models

Abstract: Liposomal anticancer agents can effectively deliver drugs to tumor lesions, but their therapeutic effects are enhanced in only limited number of patients. Appropriate biomarkers to identify responder patients to these liposomal agents will improve their treatment efficacies. We carried out pharmacological and histopathological analyses of mouse xenograft models bearing human ovarian cancers (Caov‐3, SK‐OV‐3, KURAMOCHI, and TOV‐112D) to correlate the therapeutic effects of doxorubicin‐encapsulated liposome (Dox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…PEGylated liposomes encapsulating 111 In-diethylene-triamine-penta-acetic acid ( 111 In-DTPA) were prepared by the lipid film hydration extrusion method as described previously. (14,19) In brief, the dried films were dispersed in 50 mM HEPES buffer (pH 7.4) containing 5% mannitol and 10 mM DTPA at 60°C and then repeatedly extruded through polycarbonate membrane filters (0.4-, 0.2-and 0.05-lm pore sizes) (GE Healthcare, Buckinghamshire, UK) to adjust their diameters to approximately 80 nm. Unencapsulated DTPA was removed by passage through a Sephadex G-50 column (GE Healthcare Japan Ltd, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…PEGylated liposomes encapsulating 111 In-diethylene-triamine-penta-acetic acid ( 111 In-DTPA) were prepared by the lipid film hydration extrusion method as described previously. (14,19) In brief, the dried films were dispersed in 50 mM HEPES buffer (pH 7.4) containing 5% mannitol and 10 mM DTPA at 60°C and then repeatedly extruded through polycarbonate membrane filters (0.4-, 0.2-and 0.05-lm pore sizes) (GE Healthcare, Buckinghamshire, UK) to adjust their diameters to approximately 80 nm. Unencapsulated DTPA was removed by passage through a Sephadex G-50 column (GE Healthcare Japan Ltd, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in the phase 3 study of PLD against doxorubicin single agent in metastatic breast cancer, no survival advantage was observed (4) despite the clear superiority of PLD in animal tumor models. Recent studies in mouse models using radionuclide SPECT imaging with In 111 -labeled liposomes and PET imaging with Zr 89 -labeled liposomes admixed with PLD have observed that higher tumor uptake of liposomes correlates with greater antitumor activity at the individual level (44, 45). These studies also show a correlation between tumor uptake and tumor microvessel density and reveal remarkable heterogeneity in liposomal tumor accumulation.…”
Section: Are We Using the Right Clinical Trial Designs And Assessments?mentioning
confidence: 99%
“…As a representation of the study, Harrington et al presented gamma camera images of three patients with three different cancers at 72 h post 111 In-DTPA labeled pegylated liposomes that showed clear depiction of tumors in all three images [ 109 ]. Molecular imaging using SPECT enabling liposomes are increasingly being investigated to diagnose various diseases including inflammation, plaques, cancers and many more [ 110 , 111 , 112 , 113 , 114 , 115 ]. Molecular imaging using radiolabeled nanoparticles is also aimed at facilitating better delivery, in vivo pharmacokinetics monitoring, as well controlled release.…”
Section: Clinical Applications Of Liposomesmentioning
confidence: 99%